Stratigraphy and sedimentology of the Cape and Karoo Sequences in the Eastern Cape Province - Johnson, M R (Rhodes University, Faculty of Science, Department of Geology, 1976)
The Cape Supergroup (Sequence) comprises three groups, embracing a total of twenty-three formations, with a maximum combined thickness of approximately 8 km. The Table Mountain Group consists of medium-grained (occasionally fine- or coarse-grained), "clean", ultra-quartzose sandstone plus subordinate fine-grained, "dirty", subfeldspathic to feldspathic sandstone, mudrock, and rhythmitite. Average total thickness is about 3000 m. The Bokkeveld Group is composed of mudrock, rhythmitite and subordinate subfeldspathic to feldspathic sandstone (generally fine-grained and "dirty"), with a maximum total thickness of over 3000 m. The Witteberg Group comprises fine- to medium-grained ultra-quartzose sandstone, icaceous streaky rhythmitite, mudrock, and one thin diamictite unit; total thickness is about 1700 m. The strata belonging to the Cape Supergroup appear to have been largely deposited under marine conditions in environments ranging from outer shelf to beach. Deltaic deposits are,however, common in the upper part of the Bokkeveld Group and the Witteberg Group, while the main sandstone units in the upper third of the Table Mountain Group may have accumulated on a coastal alluvial plain. Deposition took place in a basin elongated in an east-west direction, with the palaeoslope inclined towards the south. Palaeocurrents were generally directed down the palaeoslope, but westerly 1 transport directions parallel to the palaeostrike and presumed shoreline are present in both the Table Mountain and Witteberg Groups. I The sedimentary rocks o~ the Karoo Sequence are subdivided into two groups (containing a total of eleven formations) and four ungrouped formations. Using the maximum thicknesses of the individual formations, a combined total thickness of about 12 km can be calculated. The sequence commences with the Dwyka Tillite, a 700-m-thick diamictite unit. The overlying Ecca Group consists of "varved" rhythmitite, dark, massive, fine- to very fine-grained ultra-lithofeldspathic sandstone and subordinate mudrock with a total thickness of 2000 - 3000 m. The Beaufort Group is composed of thick mudstone layers alternating with thinner fine-grained ultra-lithofeldspathic, lithofeldspathic and lithic sandstones, with the exception of the Katberg Formation which consists largely of sandstone. Fining-upward cycles are ubiquitous, while red mudstone is com~on, especially in the upper half of the group. A maximum thickness of about 6000 m was obtained in the East London area. The Molteno Formation Consists of up to 600 m of alternating fine- to coarse-grained sublithic sandstones (frequently pebbly) and grey mudstones, generally forming finingupward cycles. The Elliot Formation (up to 500 m thick) consists of red and grey mUdstones and subordinate fine-grained lithofeldspathic sandstones arranged in fining-upward cycles. The bulk of the Clarens Sandstone consists of very fine-grained massive (occasionally cross-bedded) sandstone, with a maximum thickness of 300 m. The Drakensberg Group, consisting of up to 1200 m of basalt with some pyroclastic intercalations near the base, caps the Karoo sedimentary succession. The deposition of the Dwyka Tillite by glacier action coincided with a major change from the generally shallow marine conditions which characterised the sedimentation of the Cape Supergroup (with the source area located on the craton to the north of the basin) to a deep linear trough receiving clastic sediments from a source area situated south and south-east of the basin. The Ecca Group,the lower half of which is characterised by the presence of "proximal" turbidite sandstones, records the gradual infilling of this basin, with deltaic conditions developing in the upper part of the group in the western half of the study area (i.e. in the Waterford Formation). The overlying strata were virtually all deposited under fluviatile conditions, the chief exceptions being a stratigraphic interval within the lower half of the Beaufort Group which appears to have formed in a large body of water, a~d the aeolian Clarens Sandstone. The fluviatile sediments were all deposite1 by rivers flowin~ towards the north and nort~-west, while the Clarens Sandstone was laid down by winds blowing from the west. The Ecca and Beaufort Group sandstones are characterised by a high rock fragment content with "felsit ic" gra ins being a prc;>minent constituent. This, together with the relative abundance of quartzfeldspar porphyry pebbles in the Katberg Sandstone unit (Beaufort Group) near East London, indicates that volcanic material probably formed a prominent part of the post-Dwyka Karoo provenance.
Keywords: Sediments (Geology) -- South Africa -- Eastern Cape; Geology, Stratigraphic; Sedimentology